The Effectiveness of Islamic Religious Education in the Universities: The Effects on the Students' Characters in the Era of Industry 4.0 - Anwar, Chairul; Saregar, Antomi; Hasanah, Uswatun; Widayanti, Widayanti (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
The fourth industrial revolution (Industry 4.0) has become a major topic worldwide. The era of Industry 4.0 stimulates the advancement of science and technology through the Internet of Things (IoT), the Internet of Services (IoS), the Internet of Data (IoD) and Cyber-Physical Systems (CPS) which resulting in the creation of smart machines or autonomous robots. The era of Industry 4.0 gets rapid response worldwide, Indonesia is no exception. The Indonesian government appeals to the nation of Indonesia technology literacy in all aspects, especially on the aspect of education. Higher education is the driving force for change. One of the efforts undertaken by universities to prepare for the fourth industrial revolution can be done by character strengthening, so that science is not value-free and there is no statement that human as a robot with no conscience. Islamic religious education plays an important role in controlling the power of Industry 4.0 through character education. The result of this research is that character building is not only done in a formal education (educational institution), but non-formal education (parents, friends, and organization) also gives a big impact to the students. In facing the era of Industry 4.0, the character building from parents, educational institutions and government are needed.